Photosynthesis-Inhibiting Activity of N-(Disubstituted-phenyl)-3-hydroxynaphthalene-2-carboxamides - Kos, Jiri; Gonec, Tomas; Oravec, Michal; Jendrzejewska, Izabela; Jampilek, Josef (Molecules (Basel, Switzerland), 2021)
A set of twenty-four 3-hydroxynaphthalene-2-carboxanilides, disubstituted on the anilide ring by combinations of methoxy/methyl/fluoro/chloro/bromo and ditrifluoromethyl groups at different positions, was prepared. The compounds were tested for their ability to inhibit photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. N-(3,5-Difluorophenyl)-, N-(3,5-dimethylphenyl)-, N-(2,5-difluorophenyl)- and N-(2,5-dimethylphenyl)-3-hydroxynaphthalene-2-carboxamides showed the highest PET-inhibiting activity (IC50 ~ 10 µM) within the series. These compounds were able to inhibit PET in photosystem II. It has been found that PET-inhibiting activity strongly depends on the position of the individual substituents on the anilide ring and on the lipophilicity of the compounds. The electron-withdrawing properties of the substituents contribute towards the PET activity of these compounds.
Keywords: Photosynthesis; herbicidy; Naphthalenes; Photosystem II Protein Complex; hydroxynaphthalene-carboxamides; Electron Transport; spinach chloroplasts; structure-activity relationships; transport elektronů; Chloroplasts; fotosyntéza; Herbicides; PET inhibition; chloroplasty; fotosystém II (proteinový komplex); naftaleny; Spinacia oleracea